2022
DOI: 10.1111/gcbb.12933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biochar amendment on soil hydrological properties and crop water use efficiency: A global meta‐analysis and structural equation model

Abstract: The regulation of soil water retention by biochar amendment has been concerned especially in cropland ecosystem. However, the quantification of biochar's effects on soil hydrological properties and crop water use efficiency (WUE) is still limited, and the factors driving the biochar effect need to be investigated. Based on a database with 681 observations, meta‐analysis and structural equation model (SEM) were employed to reveal how biochar amendment affects water supply capacity and WUE. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…In the BI method, the IWUE varied from 3.09 to 3.12 kg kg –1 in NB 0 , while the N fertilizer with biochar doses (NB 1 , NB 2 , and NB 3 ) showed higher IWUE, ranging from 3.24 to 3.43 kg kg –1 . These results are consistent with Wu et al. (2022) and Ullah et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the BI method, the IWUE varied from 3.09 to 3.12 kg kg –1 in NB 0 , while the N fertilizer with biochar doses (NB 1 , NB 2 , and NB 3 ) showed higher IWUE, ranging from 3.24 to 3.43 kg kg –1 . These results are consistent with Wu et al. (2022) and Ullah et al.…”
Section: Discussionsupporting
confidence: 91%
“…In the BI method, the IWUE varied from 3.09 to 3.12 kg kg -1 in NB 0 , while the N fertilizer with biochar doses (NB 1 , NB 2 , and NB 3 ) showed higher IWUE, ranging from 3.24 to 3.43 kg kg -1 . These results are consistent with Wu et al (2022) and Ullah et al (2020) studies; they reported an increased IWUE with the use of biochar and found that biochar maintained soil moisture by decreasing water loss via evapotranspiration, enhanced photosynthetic efficiency, and promoted chlorophyll synthesis and biomass accumulation. Similar to this, under the DI method, the IWUE varied from 5.18 to 5.35 kg kg -1 in NB 0 , while the N fertilizer with biochar doses exhibited higher IWUE, ranging from 5.50 to 5.94 kg kg -1 .…”
Section: Methodssupporting
confidence: 92%
“…By performing the comparative analysis of grain-production water footprint in Northwest China and the national average level, it could be seen that grainirrigation-water productivity in this region was still lower than the national average, that is, its production water footprint was larger than the national average, indicating that it still had great water-saving potential [3]. The goal of reducing the regional grain-cropproduction water footprint could be achieved with the following strategies: (a) We should increase the support for irrigation and water-conservancy infrastructure; vigorously promote agricultural mechanization [41]; and promote water-saving irrigation technology, such as drip irrigation [42][43][44], sprinkler use [45,46], direct root-zone irrigation [47], deficit irrigation [9,13,48], alternate partial root-zone irrigation [13], negative-pressure irrigation [49], the application of crop close planting [50], intercropping [51], film mulching [18,42,50,52] and biochar application [53,54] in the fields, thus improving the utilization efficiency of blue-water and green-water resources from the perspective of crop physiology. New drought-resistant crops could also be cultivated [15,55].…”
Section: Measures To Effectively Reduce the Water Footprint Of Crop P...mentioning
confidence: 99%
“…The soil amended with biochar has enhanced porosity compared to the unamended soil (Githinji, 2014 ; Agegnehu et al, 2017 ; Esmaeelnejad et al, 2017 ). The pores within biochar particles as well as between biochar and soil particles increase the overall porosity of soil upon application of biochar (Agegnehu et al, 2017 ; Esmaeelnejad et al, 2017 ; Wu et al, 2022 ). Thus, the combined treatment has the potential to synergistically improve the physical structure of saline-alkali soil (sandy soil) in terms of the total soil porosity.…”
Section: Resultsmentioning
confidence: 99%